Surveying livelihoods, service delivery and governance: baseline evidence from South Sudan (Tufts Archival Research Center, 2018)
Surveying livelihoods, service delivery and governance: baseline evidence from South Sudan. Working Paper 21, by Marco d'Errico, Karolina Kozlowska, and Daniel Maxwell